An Empirical Study of the Cost of Convertible Securities - Knutson, Peter H. (Journal of Accounting Research, 1971)
Most textbooks call convertible bonds and convertible preferred stocks hybrid securities because they have the characteristics of senior securities together with many of the attributes of common stocks. In most, if not all, balance sheets they are classified as senior securities and their claim against earnings is reported to be the coupon interest or the dividends declared.' Yet, in most cases the nominal rates of return on these securities are substantially below those of equivalent-risk nonconvertible securities. It is apparent that these nominal rates are an inadequate measure of the real cost of convertible securities to the firm.2 What then is the cost of convertibles? To what extent do published reports understate or overstate their cost? What are the important variables affecting that cost? How does the cost of debt affect earnings per share? This paper presents the results of an empirical study intended to answer those questions. It seems clear that a convertible security, either bond or stock, derives its value from the magnitude of its share of the firm's earnings, present and future. That share however is not limited to the cash payout alone; it also includes a pro-rata, per equivalent common share portion of the current period earnings retained by the firm. To the extent that earnings